Demographic and clinical profile of brought in dead cases to pediatric emergency department of a tertiary care hospital - Gupta, Ratan; Tiwari, Priyanka; Roy, Manas Pratim; Khalil, Sumaira; Kashyap, Archana (Indian Journal of Child Health, 2019)
Background: The incidence of brought in dead (BID) is high in tertiary hospitals, but there is a lack of proper audit and relevant data of these cases. Objective: The current study aimed to assess the demographic characteristics and clinical profile of BID patients presenting in emergency department (ED) of a tertiary hospital. Materials and Methods: This was a retrospective observational study. All children between 0 and 12 years who were BID at the pediatric ED in a tertiary hospital between February 2018 and December 2018 were included. Data were collected on demography, history of illness, treatment seeking history, and details about transport to the hospital. Microsoft Excel was used for analysis. Results: A total of 64 BID cases were included in the study, of which 39% cases belonged to the neonatal age group. Most of the referrals were from government hospitals. Of total neonatal deaths, 44% were preterm babies; 52% of neonates had a previous history of hospitalization. Among previously hospitalized cases, 56% were discharged and 22% took their child against medical advices. Conclusion: It is crucial that the government reinforces the measures to avoid the existence of clandestine health centers. Improving referralcounter-referral system will permit the limitation of fatal medical errors. This study expects to bring the focus on BID so that future studies explore the possible strategies to contain this problem.